ANALISIS HUBUNGAN ANTARA PEMBANGUNAN EKONOMI DAERAH, KEBIJAKAN PUBLIK, DAN KESEMPATAN KERJA SEKTORAL DI JAWA TIMUR - Ashar, Khusnul; Supartono, -; Wahyudi, Setyo Tri (Journal of Indonesian Applied Economics, 2007)
This research  tries  to  reach 2 points:  the relationship between public policy andemployment in East Java, and the contribution  to government economic policy inEast Java. The research found that the East Java economic development has beenmore supported by foreign capital then by domestic one. The employment elasticityis  high means  that  capital ploughed  in  investment  created  significant  inrease  inemployment. The  leading sectors  in East Java   economy were Industry,  trade andagriculture.Keywords: Public Policy, government policy, Investment, Employment